Integrated project management system of scientific and technical centre in oil company "Rosneft" - Chetverikov V. V.; Gordievskikh V. V.; Gromakov E. I. Evgeny Ivanovich; Malishenko (Malyshenko) A. M. Alexanedr Maximovich; Voronin A. V. Aleksandr Vasilyevich; Galaktionov E. A. (Control, computer engineeringand information science, 2007)
Заглавие с титульного листа